Efficacy of pembrolizumab in advanced cancer of the vulva: a systematic review and single-arm meta-analysis - Schwab, Roxana; Schiestl, Lina Judit; Cascant Ortolano, Lorena; Klecker, Philip Herbert; Schmidt, Mona Wanda; Almstedt, Katrin; Heimes, Anne-Sophie; Brenner, Walburgis; Stewen, Kathrin; Schmidt, Marcus; Hasenburg, Annette (Frontiers in Oncology, 2024)
Vulvar cancer carries a favourable prognosis in early stages. However, therapeutic options for advanced or recurrent cases are limited despite a variety of therapeutic modalities, such as extensive surgical resection, chemotherapy, and radiotherapy. The most important emerging treatment modalities are immune checkpoint inhibitors. This systematic review and meta-analysis aims to assess the efficacy and safety of pembrolizumab, an immune checkpoint inhibitor, in women with advanced vulvar cancer.